High-manganese and nitrogen stabilized austenitic stainless steel (Fe-18Cr-22Mn-0.65N): A material with a bright future for orthopedic implant devices - Kumar C.S.; Singh G.; Poddar S.; Varshney N.; Mahto S.K.; Podder A.S.; Chattopadhyay K.; Rastogi A.; Singh V.; Mahobia G.S. (My University, 2025)
The rationale behind the success of nickel free or with extremely low nickel austenitic high manganese and nitrogen stabilized stainless steels is adverse influences of nickel ion on human body. Replacement of nickel by nitrogen and manganese provides a stable microstructure and facilitates better biocompatibility in respect of the conventional 316L austenitic stainless steel (316L SS). In this investigation, biocompatibility of the high-manganese and nitrogen stabilized (Fe-18Cr-22Mn-0.65N) austenitic stainless steel was studied and found highly promising. In vitro cell culture and cell proliferation (MTT) assays were performed on this stainless steel and assessed in respect of the 316L SS. Both the steels exhibited similar cell growth behavior. Furthermore, an enhancement was observed in cell proliferation on the Fe-18Cr-22Mn-0.65N SS after surface modification by ultrasonic shot peening (USP). The mean percent proliferation of the MG-63 cells increased from ≈88% for Un-USP to 98% and 105% for USP 3-2 and USP 2-2 samples, respectively for 5 d of incubation. Interestingly, in vivo animal study performed in rabbits for 3 and 6 weeks showed callus formation and sign of union without any allergic reaction. © 2021 IOP Publishing Ltd.